1981
DOI: 10.1111/j.1442-9071.1981.tb01495.x
|View full text |Cite
|
Sign up to set email alerts
|

An Ophthalmic Review of Cerebral Palsy in Queensland 1980

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…More importantly to postural and gait training, the muscles of the eyes and muscles controlling movement of the head also have poor coordination and therefore vision is impaired. Black [9] and O'Malley et al [10] studied ocular defects in children with cerebral palsy and found that they occurred in most (75%) children. This was associated with a loss of the ability to move the eyes from side to side (slow gaze) [11] and flaws in the vestibular ocular reflex [10,12].…”
Section: Introductionmentioning
confidence: 98%
“…More importantly to postural and gait training, the muscles of the eyes and muscles controlling movement of the head also have poor coordination and therefore vision is impaired. Black [9] and O'Malley et al [10] studied ocular defects in children with cerebral palsy and found that they occurred in most (75%) children. This was associated with a loss of the ability to move the eyes from side to side (slow gaze) [11] and flaws in the vestibular ocular reflex [10,12].…”
Section: Introductionmentioning
confidence: 98%